Ultrasound-based techniques for the diagnosis of liver steatosis - Ferraioli, Giovanna; Soares Monteiro, Livia Beatriz (World journal of gastroenterology : WJG, 2019)
Non-alcoholic fatty liver disease (NAFLD) is the leading cause of diffuse liver disease. An accurate estimate of the fat in the liver is important in the diagnostic work-up of patients with NAFLD because the degree of liver steatosis is linked to the metabolic syndrome and the cardiovascular risk. Ultrasound (US) B-mode imaging allows to subjectively estimate the fatty infiltration in the liver; however, it has a low performance for the detection of mild steatosis. Quantitative US is based on the analysis of the radiofrequency echoes detected by an US system, and it allows to calculate a backscatter coefficient or an attenuation coefficient or the sound speed. The estimation of the backscatter coefficient is rather cumbersome and requires the use of a phantom for addressing all sources of variability. Controlled attenuation parameter (CAP) available on the FibroScan system (Echosens, France) measures the attenuation of the US beam. CAP is accurate in grading fatty infiltration-even though there is an overlap between consecutive grade of liver steatosis-and the values are not influenced by liver fibrosis. Several US manufacturers are developing or have already developed software for quantifying the attenuation of the US beam. Preliminary results show that proprietary technologies implemented in US systems seem more accurate than CAP for grading liver steatosis. Another available method for quantifying liver steatosis is based on the computation of the sound speed and the initial results appear promising.